The many questions about mini chromosomes in colletotrichum spp. - Plaumanns, Peter Louis; Koch, Christian (Plants, 2020)
Many fungal pathogens carry accessory regions in their genome, which are not required for vegetative fitness. Often, although not always, these regions occur as relatively small chromosomes in different species. Such mini chromosomes appear to be a typical feature of many filamentous plant pathogens. Since these regions often carry genes coding for effectors or toxin-producing enzymes, they may be directly related to virulence of the respective pathogen. In this review, we outline the situation of small accessory chromosomes in the genus Colletotrichum, which accounts for ecologically important plant diseases. We summarize which species carry accessory chromosomes, their gene content, and chromosomal makeup. We discuss the large variation in size and number even between different isolates of the same species, their potential roles in host range, and possible mechanisms for intra-and interspecies exchange of these interesting genetic elements.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Accessory region; B-chromosome; Dispensable chromosome; Effector; Lineage-specific region; Mini chromosome; Plant pathogens; Virulence chromosome